2016
DOI: 10.1007/s10995-016-2181-z
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Decision Making Related to Pregnancy Among Young Women with Cystic Fibrosis

Abstract: Introduction The number of female patients with CF able to consider pregnancy has increased with improved therapies. This study explored attitudes and decision making regarding pregnancy among young women with CF. Methods Twenty-two women with CF ages 18-30 years completed semi-structured, in-person interviews exploring experiences with preconception counseling and reproductive care in the CF setting. Interviews were audio-recorded, transcribed, and coded using a thematic analysis approach. Results Participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
62
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 34 publications
3
62
0
Order By: Relevance
“…Another explanation could be that pregnancy is now well prepared for by CF women and care providers, leading to optimal preconception care and close monitoring of pulmonary exacerbations and nutritional status according to published guidelines (16). However, as highlighted by recent studies, reproductive decision making is complex for both young women with CF and care providers, particularly concerning CF women with complicated clinical conditions such as CFRD (17,18); the data reported in the present study provide some information to help the decision making.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another explanation could be that pregnancy is now well prepared for by CF women and care providers, leading to optimal preconception care and close monitoring of pulmonary exacerbations and nutritional status according to published guidelines (16). However, as highlighted by recent studies, reproductive decision making is complex for both young women with CF and care providers, particularly concerning CF women with complicated clinical conditions such as CFRD (17,18); the data reported in the present study provide some information to help the decision making.…”
Section: Discussionmentioning
confidence: 99%
“…The median (range) rate of FEV 1 decline in diabetic women was À6.03 (À23.31 to 4.94) and in non-diabetic women À2.03 (À61 18. YÀ1: one year before pregnancy; Y+1: one year after pregnancy; Y+2: two years after pregnancy.…”
mentioning
confidence: 99%
“…While research in CF has demonstrated an essentially neutral impact of pregnancy on health , the data indicate that individuals with CF lack important CF‐specific reproductive health knowledge . Women with CF have exhibited limited awareness and misconceptions of the physical and psychosocial implications of pregnancy and parenthood with this chronic illness; they have also described inadequacies of reproductive health communication from CF providers, including the delayed introduction of reproductive health education, as well as disheartening disapproval of childbearing by CF providers . The only known study on CF‐related reproductive health education including men suggests that deficiencies also exist in education from CF care teams on these topics …”
Section: Introductionmentioning
confidence: 99%
“…Normalcy has also arisen as an important theme in CF SRH. In a prior qualitative study, adult women with CF voiced a desire for normalcy and autonomy in reproductive decision making and pregnancy planning . In addition, as nearly eighty percent of U.S. adolescent and young adult women with CF desired future children, it appears that adolescent girls with CF are growing up with expectations for their reproductive lives similar to their healthy peers .…”
Section: Discussionmentioning
confidence: 99%